Biomekhanicheskaya diagnostika optimal'nogo vypol'neniya tsiklicheskikh dvizhenii - Zhilyayev, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this research was to offer the quantitative biomechanical criterion of an estimation of an optimal technique of cyclic movements execution based on the minimization of the correctional movements the at performance of the put task. The author investigated the walking of 69 healthy, physically not trained men in the age of 20 to 55 years. As against a traditional method of research of the dynamic parameters of walking consisting in unitary registration of the reaction of a support, the author investigated a vertical component of the reaction of a support in a series from 10 steps of each examinee. All surveyed examinees were divided into age groups. The result of the research has allowed to make a conclusion that the variativity of the researched biomechanical parameters is less on the party of conducting limb (with the greater force of pushing away) in all age groups of the examinees. The given result has allowed to assume, that the functional condition of basic limb muscles with the greater force of pushing is a little bit higher, than at another limb.